Orchestrating backward linkages from the extractive sector to other productive value adding sectors : a case study of the mining and the manufacturing industries in Zambia - Nsupila, Maybin (Graduate School of Development Policy and Practice, 2016)
The quest for natural resource-based industrialisation has continued in many countries, particularly in Sub Sahara Africa. Zambia, a resource rich country, mainly dependent on copper for its exports, has been trying to industrialise with limited success. Recently, there has been renewed emphasis on leveraging the growth recorded in the mining industry to develop other economic sectors. However, the focus of the discourse has mainly been on building effective fiscal linkages. In this thesis, I argue that beyond fiscal linkages, Zambia can develop the local manufacturing industry through backward linkages from mining to manufacturing given the huge manufactured input demand in the mining sector. I investigate factors driving linkage development and establish that government, lead mining companies, local manufacturing firms, private sector associations and donors all have roles to play in the process. While government has the responsibility of putting in place the appropriate policy and regulatory framework to encourage local procurement, as well as create a conducive environment for attracting investment and fostering development of manufacturing firms, lead mining firms could contribute by ensuring they make it easy and provide adequate procurement opportunities to local manufacturing firms. They could also contribute by using part of their profits to implement development activities and corporate social responsibility programmes geared towards building capacities of suppliers to meet their drivers of procurement decisions. Further, local manufacturing firms can play a role by adopting strategies that help them upgrade capabilities to meet the key supply requirements for the mining industry. Associations too can play a significant role. Among other things, the Zambia Chamber of Mines can contribute to this effort by ensuring that a common approach with regard to local procurement is adopted by the mining firms thus making easy for local manufacturers to do business with the mines. The Zambia Association of Manufacturers can play the role of policy advocacy, coordinate the response and engagement from the manufacturers as well as stage activities that facilitate the building of business relations with mining firms. Donors can work with government in improving the policy environment, support local companies' capacity upgrading efforts as well as work with associations in their advocacy and other activities geared towards increasing valued-added local procurement.